2004
DOI: 10.1590/s0100-879x2004000200007
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of chlorhexidine digluconate to murine macrophages and its effect on hydrogen peroxide and nitric oxide induction

Abstract: Chlorhexidine, even at low concentrations, is toxic for a variety of eukaryotic cells; however, its effects on host immune cells are not well known. We evaluated in vitro chlorhexidine-induced cytotoxicity and its effects on reactive oxygen/nitrogen intermediate induction by murine peritoneal macrophages. Thioglycollate-induced cells were obtained from Swiss mice by peritoneal lavage with 5 ml of 10 mM phosphate-buffered saline, washed twice and resuspended (10 6 cells/ ml) in appropriate medium for each test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…These results are similar to other [33] in neutrophils from rats fed a soybean-rich diet. H 2 O 2 is an important citotoxic agent [34] and its lower release could contribute to the anti-inflammatory effect of the hyperlipidic diets, as observed previously [12,27] and reproduced in the present study. Some reports have shown decreased activity of superoxide-dismutase (SOD), the enzyme catalyzing H 2 O 2 formation, in plasma and in different tissues of animals treated with nY3 or nY6 PUFA-rich diets [35,36].…”
Section: Discussionsupporting
confidence: 90%
“…These results are similar to other [33] in neutrophils from rats fed a soybean-rich diet. H 2 O 2 is an important citotoxic agent [34] and its lower release could contribute to the anti-inflammatory effect of the hyperlipidic diets, as observed previously [12,27] and reproduced in the present study. Some reports have shown decreased activity of superoxide-dismutase (SOD), the enzyme catalyzing H 2 O 2 formation, in plasma and in different tissues of animals treated with nY3 or nY6 PUFA-rich diets [35,36].…”
Section: Discussionsupporting
confidence: 90%
“…However, in vitro studies have shown chlorhexidine to be highly cytotoxic even in low concentration to many cell types, including gingival fibroblasts [39], macrophages [40], and osteoblastic and endothelial cells [41]. Other studies have also shown that topical application of chlorhexidine may result in its penetration through the epithelial barrier, thus triggering tissue damage [42].…”
Section: Discussionmentioning
confidence: 99%
“…BisGMA with its hydrophobic property needs organic solvents to facilitate absorbtion in a hydrophilic environment for biocompatibility studies. Macrophages have been used for immunocytotoxicity testing because they permit the measurement of cytotoxic responses directly in cell culture and because of their ability to maintain immunological functions in the presence of many chemical agents (Bonacorsi et al. 2004); thus, RAW264.7 cells were selected in this study.…”
Section: Discussionmentioning
confidence: 99%